Pengaruh Nilai Taro Ada Taro Gau dalam Parenting Bugis terhadap Karakter Tanggung Jawab Anak di SD Negeri 124 Lura - Syahrul Asyura; Juntika Nurihsan; Eka Sakti Yudha (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the effect of the application of Taro Ada Taro Gau cultural values in Bugis parenting patterns on the formation of children's responsibility character at SD Negeri 124 Lura. Taro Ada Taro Gau is a Bugis cultural principle that emphasizes consistency between words and actions, and prioritizes moral and social responsibility. This study used a quantitative approach with a quasi-experimental design of one group pretest-posttest type. The research subjects consisted of 20 children and Bugis parents. Data collection was conducted through a questionnaire that was compiled based on the character indicators of responsibility according to Albert Bandura's theory. Data analysis used paired sample t-test. The test results showed a significant influence between the application of Taro Ada Taro Gau values in parenting on improving children's responsibility character, with a tcount value of 15.742> ttable 2.093 and a significance value of 0.00 < 0.05. This finding confirms that integrating local cultural values in parenting is effective in shaping children's responsible character.